Penerapan Metode Role Playing untuk Meningkatkan Rasa Percaya Diri Siswa Kelas V di Sekolah Dasar - Fajar Herdiansyah; Ilyas Idris (Morfologi : Jurnal Ilmu Pendidikan, Bahasa, Sastra dan Budaya, 2025)
This research was conducted based on observations made on fifth-grade students, regarding their self-confidence, which still requires stimulation due to a lack of self-confidence. Based on this problem, an improvement is needed that can enhance students' self-confidence through engaging and enjoyable activities that are not frequently done, one of which is the role-playing method. The objective of this research is to determine the increase in self-confidence of fifth-grade students through the role-playing method at SD Negeri 26/IV Kota Jambi. This research is a Classroom Action Research (CAR). It was conducted at SD Negeri 26/IV Kota Jambi from March 2025 to April 2025. The research subjects were 15 students and the class teacher. Data collection methods included observation, documentation, and interviews. Data analysis involved data collection, data reduction, data presentation, and drawing conclusions. The performance indicator to be achieved is an increase in children's self-confidence by 75% out of 15 children using the role-playing method. The results of this study indicate that the role playing method is proven to be effective in increasing the self-confidence of fifth grade students at SDN 26/IV Jambi City. The increase in children's self-confidence can be seen from cycle I to cycle II. In cycle I, the children's self-confidence ability was categorized as developing well by 44% with a good category. and in cycle II it increased to 94% with a very good category. So it can be concluded that the role playing method can increase self-confidence in fifth grade students at SDN 26/IV Jambi City.